Millenial Employees Perception Related to Workload, Work Life Balance, Challenge Leadership on Happiness at Work Case Study Kuningan Area South Jakarta - Diyah Ayu Aprita Sari; MC Oetami Prasadjaningsih (DINASTI RESEARCH, 2023)
The purpose of this study is to analyze the perception millenial employees about workload, work life balance and challange leadership on happiness at work. This study used quantitative data types with the population of this study are employees worked in Kuningan Area South Jakarta. The sample used in this study are 100 respondents. The methode used for data collection is by used a questionnaire distribution technique trough google form. The analysis technique in this study used the inner model andouter model test wich were processed and analyzed using SmartPLS software which is equipped with variable descriptions of each respondent’s characteristics. The results of this study showed that the workload had a significant effect on happiness at work, work life balance had a significant effect on happiness at work, challenge leadership had a significant effect on happiness at work, workload had no significant effect on challenge leadership, work life balance had a significant effect on leadership. Concequently millenials do not query about workload but work life balance are the primary reason, and challange leadership to experience hapiness at work.